2012
DOI: 10.1136/bmjqs-2011-000585
|View full text |Cite
|
Sign up to set email alerts
|

Comparative economic analyses of patient safety improvement strategies in acute care: a systematic review

Abstract: BackgroundThe objective was to systematically review comparative economic analyses of patient safety improvements in the acute care setting.MethodsA systematic review of 15 patient safety target conditions and six improvement strategies was conducted. The authors searched the published literature through Medline (2000–November 2011) using the following search terms for costs: ‘costs and cost analysis’, ‘cost-effectiveness’, ‘cost’ and ‘financial management, hospital’. The methodological quality of potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 52 publications
0
37
0
1
Order By: Relevance
“…Surveys of the anesthesia, critical care, and perioperative literature reveal that there are very few economic analyses published in our field despite increasing recognition of the need. 19,27,28 It is an opportune time for anesthesiologists and clinical leaders to become familiar with the tools and methodologies of health economics in order to facilitate decision-making. When a drug, device, or procedure comes to market in Canada, there is no guarantee that it represents good value for money compared with the next best alternative.…”
Section: Increasing Capacity For Health Economics In Anesthesiamentioning
confidence: 99%
“…Surveys of the anesthesia, critical care, and perioperative literature reveal that there are very few economic analyses published in our field despite increasing recognition of the need. 19,27,28 It is an opportune time for anesthesiologists and clinical leaders to become familiar with the tools and methodologies of health economics in order to facilitate decision-making. When a drug, device, or procedure comes to market in Canada, there is no guarantee that it represents good value for money compared with the next best alternative.…”
Section: Increasing Capacity For Health Economics In Anesthesiamentioning
confidence: 99%
“…In addition, as previously established (34,176), our review finds that a rigorous, quantitative demonstration of the relationship between an intervention and outcomes remains rare. Although one could easily dismiss research designs other than randomized clinical trials as less rigorous and call for stronger analytical methods for evaluation, our investigation suggests some caveats to this typical conclusion.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Our review focuses specifically on hospital errors because this is where the bulk of intervention efforts have been directed and where the measurement of errors is most developed. To distinguish our review from other excellent recent reviews of interventions designed to reduce organizational errors in the health care context (34,176), we focus explicitly on interventions that reduce errors by directly or indirectly impacting safety culture. This allows us to categorize these activities using a theoretical model that shows how interventions may work together to shape safety climate and safety culture in a process that reduces hospital errors over time.…”
Section: Introductionmentioning
confidence: 99%
“…When examining strategies to improve medication history taking, electronic medication reconciliation and medication reconciliation (generally defined as the process of obtaining and maintaining a complete and accurate list of the current medication use of an individual across the healthcare settings) performed by pharmacists instead of physicians are effective. Pharmacy‐based medication reconciliation has been shown to be one of four cost‐effective strategies (out of a total of 21) to improve patient safety . When pharmacists perform medication reconciliation in the ED, a recent study including 3,594 medication histories showed that 59% of the medication histories that pharmacists took were different from those that physicians took .…”
mentioning
confidence: 99%